Ultrathin anti-oxidation stainless steel band

By optimizing the element composition and plating the electroplating corrosion-resistant layer and oxidation-resistant coating in the stainless steel strip, the problem of insufficient oxidation resistance in extreme environments is solved, and higher tensile strength, corrosion resistance and oxidation resistance are achieved.

CN119592880AActive Publication Date: 2025-03-11JIANGSU GUANSEN NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411644322.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-11
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

It is difficult for existing stainless steel belts to maintain good oxidation resistance for a long time in extreme environments, so they need to be improved.

Method used

The ultra-thin stainless steel strip is used to design the composition and proportion of elements in the stainless steel strip to reduce the content of harmful elements oxygen and sulfur, and the surface is coated with electroplating corrosion-resistant layers and antioxidant coatings, combining active corrosion-resistant and passive corrosion-resistant mechanisms.

Benefits of technology

It significantly improves the tensile strength, corrosion resistance and oxidation resistance of stainless steel belts, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139306110000091
    Figure BDA0005139306110000091
Patent Text Reader

Abstract

The invention relates to an ultra-thin anti-oxidation stainless steel band, and relates to the technical field of metal materials, the ultra-thin anti-oxidation stainless steel band comprises an ultra-thin stainless steel band matrix, an electroplating corrosion-resistant layer and an anti-oxidation coating, the ultra-thin stainless steel band matrix comprises the following components in parts by mass: 2.5-3.5% of nickel, 6-8% of aluminum, 3.5-4.5% of zinc, 2-6% of tin, 0.05-0.1% of boron, 0.02-0.05% of bismuth, 0.05-0.07% of cobalt, 1.5-3% of manganese, 0.02-0.05% of phosphorus, 0.06-0.1% of lanthanum, and the balance of stainless steel. And the balance of iron and inevitable impurities. The preparation method of the ultrathin anti-oxidation stainless steel band comprises the following steps: preparing an ultrathin stainless steel band substrate; the method comprises the following steps: pretreating an ultrathin stainless steel band substrate, and immersing the pretreated stainless steel band in a plating solution for electroplating treatment to obtain a stainless steel band with an electroplated corrosion-resistant layer; mixing an antioxidant coating and a curing agent, coating the surface of the stainless steel band with the electroplated corrosion-resistant layer with the mixture, and heating and curing after the coating is aired to obtain the ultrathin antioxidant stainless steel band. The method has the effect of improving the oxidation resistance, corrosion resistance and tensile strength of the stainless steel band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal materials, and in particular to an ultra-thin anti-oxidation stainless steel strip. Background Art

[0002] As a high-performance material, stainless steel strip has broad application prospects in the fields of electronics, precision instruments and medical devices. With the development of industrial technology and the increase in market demand, users have put forward higher requirements on the performance of materials, requiring not only good corrosion resistance and oxidation resistance, but also high mechanical strength and ultra-thin properties to meet the needs of precision manufacturing and lightweight design.

[0003] Related technologies coat the surface of stainless steel substrates with corrosion-resistant layers, such as metal coatings or ceramic coatings, to increase the surface corrosion resistance to improve the material's antioxidant capacity; or modify the stainless steel substrate, such as alloying treatment, that is, adding antioxidant elements to the stainless steel substrate components to improve its antioxidant performance. These technologies have improved the antioxidant performance of stainless steel strips to a certain extent, but the antioxidant performance achieved by a single alloying treatment or electroplating treatment is limited, and the prepared stainless steel strips are difficult to maintain good working performance for a long time in extreme environments, so there is room for improvement. Summary of the invention

[0004] In order to improve the anti-oxidation performance of a stainless steel strip, the present application provides an ultra-thin anti-oxidation stainless steel strip.

[0005] The ultra-thin anti-oxidation stainless steel strip provided in this application adopts the following technical solution: An ultra-thin anti-oxidation stainless steel strip comprises an ultra-thin stainless steel strip substrate, an electroplated corrosion-resistant layer and an anti-oxidation coating. The ultra-thin stainless steel strip substrate comprises the following components in fractions by mass: 2.5-3.5% nickel, 6-8% aluminum, 3.5-4.5% zinc, 2-6% tin, 0.05-0.1% boron, 0.02-0.05% bismuth, 0.05-0.07% cobalt, 1.5-3% manganese, 0.02-0.05% phosphorus, 0.06-0.1% lanthanum, and the balance is iron and unavoidable impurities.

[0006] By designing the composition and ratio of elements in the stainless steel strip, the content of harmful elements oxygen and sulfur in the stainless steel strip can be effectively reduced, the state of inclusions can be improved, and the tensile strength, corrosion resistance and oxidation resistance of the stainless steel strip can be improved; the electroplated corrosion-resistant layer obtains an alloy coating by co-depositing alloy elements on the surface of the stainless steel strip, and the synergistic effect produces solid solution strengthening, thereby improving the toughness, oxidation resistance and corrosion resistance of the electroplated corrosion-resistant layer; the anti-oxidation coating adheres evenly and firmly to the surface of the electroplated corrosion-resistant layer, and through the combination of active anti-corrosion and passive anti-corrosion principles, it effectively protects the stainless steel strip, improves the corrosion resistance and oxidation resistance of the stainless steel strip, and extends the service life of the stainless steel strip.

[0007] Preferably, the anti-oxidation coating is obtained by coating an anti-oxidation coating on the surface of the electroplated corrosion-resistant layer, and the raw materials for preparing the anti-oxidation coating include metal organic framework material corrosion inhibitor, modified polyvinylidene fluoride, zinc phosphate, epoxy resin and solvent.

[0008] By using metal organic framework materials to load corrosion inhibitors, the intelligent and controllable release of corrosion inhibitors can be achieved. The metal organic framework materials participate in the curing reaction of the coating through the metal cation center and the active sites on the organic ligands, becoming a part of the coating, having good stability, and can reinforce the defects of the coating and improve the barrier properties of the coating; modified polyvinylidene fluoride has low surface energy and good system compatibility, which can improve the hydrophobicity of the surface, reduce the impact of humid environment and corrosive media on stainless steel strips, and improve the antioxidant properties; zinc phosphate can synergistically work with metal organic framework material corrosion inhibitors to play a role of isolation and protection, isolating oxygen, corrosive media and moisture, reducing the penetration of electrolytes, and improving the adhesion, durability, antioxidant properties and corrosion resistance of the coating.

[0009] Preferably, the raw materials for preparing the metal organic framework material corrosion inhibitor include metal organic framework material and corrosion inhibitor, the raw materials for preparing the metal organic framework material include benzotriazole, 5-tert-butylisophthalic acid, zinc nitrate hexahydrate and graphene oxide, and the corrosion inhibitor includes 8-hydroxyquinoline.

[0010] Benzotriazole and 5-tert-butylisophthalic acid, as organic ligands, can construct stable metal-organic framework materials with zinc ions. Benzotriazole itself also has good corrosion inhibition properties. It forms a dense adsorption film with the metal surface through π-π bonds and electrostatic interactions, which plays a role of isolation and protection, inhibiting the occurrence of oxidation and corrosion reactions; graphene oxide has a two-dimensional sheet structure, has a shielding effect, and can provide passive protection. By doping metal-organic framework materials with graphene oxide, benzotriazole can be effectively wrapped and protected, so that the active protection of the corrosion inhibitor is combined with the passive protection of graphene oxide, thereby improving the durability, antioxidant and corrosion resistance of the coating; 8-Hydroxyquinoline has good corrosion inhibition properties and can be loaded by metal-organic framework materials, synergistically with them to prolong the time of corrosion inhibition effect, thereby improving the antioxidant and corrosion resistance of stainless steel strips.

[0011] Preferably, the mass ratio of the benzotriazole, 5-tert-butylisophthalic acid, zinc nitrate hexahydrate and graphene oxide is 0.2:0.19:1:(0.008-0.012).

[0012] The metal organic framework material prepared according to the above mass ratio has good antioxidant properties, corrosion resistance and system compatibility.

[0013] Preferably, the modified polyvinylidene fluoride is prepared by the following steps: The polyvinylidene fluoride and sodium hydroxide are dispersed in an ethanol aqueous solution and heated and stirred to react to obtain a modified solution, and the modified solution is dried under heating conditions to obtain modified polyvinylidene fluoride.

[0014] By modifying polyvinylidene fluoride with sodium hydroxide, the system compatibility of polyvinylidene fluoride can be improved, the modified polyvinylidene fluoride and epoxy resin can be fully cross-linked, the hydrophobicity of the polymer organic phase in the coating can be improved, and thus the antioxidant performance can be improved.

[0015] Preferably, the ultra-thin anti-oxidation stainless steel strip is prepared by the following steps: An ultra-thin stainless steel strip substrate is prepared; the ultra-thin stainless steel strip substrate is pretreated, and after polishing, degreasing, pickling, water washing and drying, a pretreated stainless steel strip is obtained; the pretreated stainless steel strip is immersed in a plating solution for electroplating treatment to obtain a stainless steel strip with an electroplated corrosion-resistant layer; an anti-oxidation coating and a curing agent are mixed and coated on the surface of the stainless steel strip with the electroplated corrosion-resistant layer, and after the coating is dried, it is heated and cured to obtain an ultra-thin anti-oxidation stainless steel strip.

[0016] The stainless steel strip prepared according to the above steps has good oxidation resistance, corrosion resistance and high tensile strength.

[0017] Preferably, the electroplated corrosion-resistant layer includes zinc, nickel, phosphorus and tungsten.

[0018] Preferably, the plating solution comprises zinc sulfate, nickel sulfamate, sodium tungstate, sodium hypophosphite, sodium citrate, boric acid and sodium dodecyl sulfate.

[0019] Zinc, nickel, phosphorus and tungsten elements have good antioxidant properties, and the zinc alloy coating obtained by co-deposition of the four can provide good corrosion protection; nickel sulfamate allows nickel ions to be more evenly dispersed on the surface of the substrate, improving the uniformity of nickel ion deposition; sodium hypophosphite can hinder the charge transfer step during the electrodeposition process, increase the degree of cathodicization, inhibit the excessive growth of the crystal nucleus, refine the grains and promote the close stacking of the grains.

[0020] Preferably, the electroplated corrosion-resistant layer is prepared by the following steps: The lead plate is used as the anode and the pretreated stainless steel strip is used as the cathode. The strip is immersed in the plating solution for electroplating operation. The temperature and time are controlled. After the electroplating is completed, the strip is washed with water and dried to obtain a stainless steel strip with an electroplated corrosion-resistant layer.

[0021] Preferably, the electroplating temperature is 50-70° C., and the electroplating time is 60-90 min.

[0022] The electroplated corrosion-resistant layer prepared according to the above steps and conditions has good density and uniformity, and can play a good corrosion protection role.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. By designing the composition and ratio of elements in the stainless steel strip, the content of harmful elements oxygen and sulfur in the stainless steel strip is effectively reduced, the state of inclusions is improved, and the tensile strength, corrosion resistance and oxidation resistance of the stainless steel strip are improved; the electroplated corrosion-resistant layer is obtained by co-depositing alloy elements on the surface of the stainless steel strip to obtain an alloy coating, and the synergistic effect produces solid solution strengthening, thereby improving the toughness, oxidation resistance and corrosion resistance of the electroplated corrosion-resistant layer; the anti-oxidation coating is evenly and firmly adhered to the surface of the electroplated corrosion-resistant layer, and through the combination of active anti-corrosion and passive anti-corrosion principles, the stainless steel strip is effectively protected, the corrosion resistance and oxidation resistance of the stainless steel strip are improved, and the service life of the stainless steel strip is extended.

[0024] 2. By using metal organic framework materials to load corrosion inhibitors, the intelligent and controllable release of corrosion inhibitors can be achieved. The metal organic framework materials participate in the curing reaction of the coating through the metal cation center and the active sites on the organic ligands, becoming a part of the coating, with good stability, and can reinforce the defects of the coating and improve the barrier properties of the coating; modified polyvinylidene fluoride has low surface energy and good system compatibility, which can improve the hydrophobicity of the surface, reduce the impact of humid environment and corrosive media on stainless steel strips, and improve the antioxidant properties; zinc phosphate can synergistically work with metal organic framework material corrosion inhibitors to play a role of isolation and protection, isolating oxygen, corrosive media and moisture, reducing the penetration of electrolytes, and improving the adhesion, durability and antioxidant properties of the coating.

[0025] 3. Zinc, nickel, phosphorus and tungsten elements have good antioxidant properties. The zinc alloy coating obtained by co-deposition of the four can provide good corrosion protection; nickel sulfamate allows nickel ions to be more evenly dispersed on the surface of the substrate, improving the uniformity of nickel ion deposition; sodium hypophosphite can hinder the charge transfer step during the electrodeposition process, increase the degree of cathodicization, inhibit the excessive growth of the crystal nucleus, refine the grains and promote the close stacking of the grains. DETAILED DESCRIPTION

[0026] The present application discloses an ultra-thin anti-oxidation stainless steel strip. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Description of raw materials: benzotriazole (CAS No.: 95-14-7), 5-tert-butylisophthalic acid (CAS No.: 2359-09-3), zinc nitrate hexahydrate (CAS No.: 10196-18-6), graphene oxide was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., 8-hydroxyquinoline (CAS No.: 148-24-3), polyvinylidene fluoride (CAS No.: 24937-79-9), epoxy resin model is E-44 (CAS No.: 61788-97-4), solvent is ethyl acetate (CAS No.: 141-78-6), zinc phosphate (CAS No.: 7543-51-3), curing agent is polyamide epoxy resin curing agent 2115, ZIF-8 (CAS No.: 59061-53-9), ZIF-8 (CAS No.: 59061-53-9).

[0027] Example 1 Preparation of metal organic framework materials 4.29 kg of benzotriazole, 4.08 kg of 5-tert-butylisophthalic acid, 21.46 kg of zinc nitrate hexahydrate and 0.17 kg of graphene oxide were mixed and dispersed in 100 L of a mixed solution of acetonitrile and water with a volume ratio of 3:1. After ultrasonication for 30 minutes, the MOF reaction liquid was obtained. The reaction was carried out in a high-temperature reactor at 120°C for 48 hours. After cooling to below 30°C, the mixture was washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C to obtain a metal organic framework material.

[0028] Preparation of metal organic framework material corrosion inhibitor 25 kg of metal organic framework material and 5 kg of 8-hydroxyquinoline were mixed and dispersed in 50 L of anhydrous ethanol, stirred at a speed of 200 rpm for 12 hours, and dried in an oven at 80° C. after centrifugation to obtain a metal organic framework material corrosion inhibitor.

[0029] Preparation of modified polyvinylidene fluoride 20 kg of polyvinylidene fluoride and 2 kg of sodium hydroxide were dispersed in 30 L of a mixed solution of ethanol and deionized water in a volume ratio of 1:1, and stirred at a speed of 200 rpm for 6 hours in a 60° C. water bath to obtain a modified solution, and the modified solution was dried in an oven at 80° C. to obtain modified polyvinylidene fluoride.

[0030] Preparation of antioxidant coatings 8 kg of modified polyvinylidene fluoride, 40 kg of epoxy resin and 15 L of solvent were mixed and dispersed to obtain a resin dispersion, 20 kg of metal organic framework corrosion inhibitor and 5 kg of zinc phosphate were added to the resin dispersion, and after stirring at a speed of 500 rpm for 1 hour, the mixture was ground to a fineness of less than 50 μm to obtain an antioxidant coating.

[0031] Preparation of ultra-thin oxidation-resistant stainless steel strip An ultra-thin stainless steel strip substrate is prepared so that the element composition of the ultra-thin stainless steel strip substrate is: nickel 2.5%, aluminum 6%, zinc 4.5%, tin 6%, boron 0.1%, bismuth 0.05%, cobalt 0.05%, manganese 1.5%, phosphorus 0.05%, lanthanum 0.1%, and the balance is iron and inevitable impurities.

[0032] The ultra-thin stainless steel strip substrate is polished, and the polished stainless steel strip is immersed in an alkaline solution at 65° C. for 10 minutes to obtain a deoiled stainless steel strip, wherein the alkaline solution is obtained by mixing 5 kg of sodium hydroxide and 1 kg of sodium bicarbonate and dispersing them in 100 L of deionized water; the deoiled stainless steel strip is immersed in a 0.1 mol / L hydrochloric acid solution for 2 minutes to obtain an acid-washed stainless steel strip, and the acid-washed stainless steel strip is washed with deionized water, and dried at 40° C. to obtain a pretreated stainless steel strip.

[0033] 9kg zinc sulfate, 5kg nickel sulfamate, 2kg sodium tungstate, 2kg sodium hypophosphite, 6kg sodium citrate, 3kg boric acid and 8g sodium dodecyl sulfate were mixed and dispersed in 100L deionized water, and stirred at 200rpm for 1h to obtain a plating solution. A lead plate was used as an anode and a pretreated stainless steel strip was used as a cathode. The plating operation was carried out by immersing the lead plate in the plating solution, and the current density was controlled to be 3A / dm 2 The electroplating temperature is 50°C, the electroplating time is 90 minutes, and after the electroplating is completed, it is washed with deionized water and dried to obtain a stainless steel strip with an electroplated corrosion-resistant layer.

[0034] The antioxidant coating and the curing agent were mixed in a mass ratio of 20:1 and coated on the surface of the stainless steel strip with the electroplated corrosion-resistant layer. After the coating was dried, it was cured at 100°C for 2h to obtain an ultra-thin antioxidant stainless steel strip.

[0035] Example 2 Preparation of metal organic framework materials 4.28 kg of benzotriazole, 4.07 kg of 5-tert-butylisophthalic acid, 21.4 kg of zinc nitrate hexahydrate and 0.25 kg of graphene oxide were mixed and dispersed in 100 L of a mixed solution of acetonitrile and water with a volume ratio of 3:1. After ultrasonication for 30 minutes, the MOF reaction solution was obtained. The reaction was carried out in a high-temperature reactor at 120°C for 48 hours. After cooling to below 30°C, the mixture was washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C to obtain a metal organic framework material.

[0036] Preparation of metal organic framework material corrosion inhibitor 25 kg of metal organic framework material and 5 kg of 8-hydroxyquinoline were mixed and dispersed in 50 L of anhydrous ethanol, stirred at a speed of 200 rpm for 12 hours, and dried in an oven at 80° C. after centrifugation to obtain a metal organic framework material corrosion inhibitor.

[0037] Preparation of modified polyvinylidene fluoride 20 kg of polyvinylidene fluoride and 2 kg of sodium hydroxide were dispersed in 30 L of a mixed solution of ethanol and deionized water in a volume ratio of 1:1, and stirred at a speed of 200 rpm for 6 hours in a 60° C. water bath to obtain a modified solution, and the modified solution was dried in an oven at 80° C. to obtain modified polyvinylidene fluoride.

[0038] Preparation of antioxidant coatings 8 kg of modified polyvinylidene fluoride, 40 kg of epoxy resin and 15 L of solvent were mixed and dispersed to obtain a resin dispersion, 20 kg of metal organic framework corrosion inhibitor and 5 kg of zinc phosphate were added to the resin dispersion, and after stirring at a speed of 500 rpm for 1 hour, the mixture was ground to a fineness of less than 50 μm to obtain an antioxidant coating.

[0039] Preparation of ultra-thin oxidation-resistant stainless steel strip An ultra-thin stainless steel strip substrate is prepared so that the element composition of the ultra-thin stainless steel strip substrate is: 3.5% nickel, 8% aluminum, 3.5% zinc, 2% tin, 0.05% boron, 0.02% bismuth, 0.07% cobalt, 3% manganese, 0.02% phosphorus, 0.06% lanthanum, and the balance is iron and inevitable impurities.

[0040] The ultra-thin stainless steel strip substrate is polished, and the polished stainless steel strip is immersed in an alkaline solution at 65° C. for 10 minutes to obtain a deoiled stainless steel strip, wherein the alkaline solution is obtained by mixing 5 kg of sodium hydroxide and 1 kg of sodium bicarbonate and dispersing them in 100 L of deionized water; the deoiled stainless steel strip is immersed in a 0.1 mol / L hydrochloric acid solution for 2 minutes to obtain an acid-washed stainless steel strip, and the acid-washed stainless steel strip is washed with deionized water, and dried at 40° C. to obtain a pretreated stainless steel strip.

[0041] 9kg zinc sulfate, 5kg nickel sulfamate, 2kg sodium tungstate, 2kg sodium hypophosphite, 6kg sodium citrate, 3kg boric acid and 8g sodium dodecyl sulfate were mixed and dispersed in 100L deionized water, and stirred at 200rpm for 1h to obtain a plating solution. A lead plate was used as an anode, and a pretreated stainless steel strip was used as a cathode. The strip was immersed in the plating solution for electroplating. The current density was controlled to be 3A / dm2, the electroplating temperature was 70℃, and the electroplating time was 60min. After the electroplating was completed, it was washed with deionized water and dried to obtain a stainless steel strip with an electroplated corrosion-resistant layer.

[0042] The antioxidant coating and the curing agent were mixed in a mass ratio of 20:1 and coated on the surface of the stainless steel strip with the electroplated corrosion-resistant layer. After the coating was dried, it was cured at 100°C for 2h to obtain an ultra-thin antioxidant stainless steel strip.

[0043] Example 3 Preparation of metal organic framework materials 4.29 kg of benzotriazole, 4.07 kg of 5-tert-butylisophthalic acid, 21.43 kg of zinc nitrate hexahydrate and 0.21 kg of graphene oxide were mixed and dispersed in 100 L of a mixed solution of acetonitrile and water with a volume ratio of 3:1. After ultrasonication for 30 minutes, the MOF reaction solution was obtained. The reaction was carried out in a high-temperature reactor at 120°C for 48 hours. After cooling to below 30°C, the mixture was washed three times with deionized water and anhydrous ethanol respectively, and dried in an oven at 80°C to obtain a metal organic framework material.

[0044] Preparation of metal organic framework material corrosion inhibitor 25 kg of metal organic framework material and 5 kg of 8-hydroxyquinoline were mixed and dispersed in 50 L of anhydrous ethanol, stirred at a speed of 200 rpm for 12 hours, and dried in an oven at 80° C. after centrifugation to obtain a metal organic framework material corrosion inhibitor.

[0045] Preparation of modified polyvinylidene fluoride 20 kg of polyvinylidene fluoride and 2 kg of sodium hydroxide were dispersed in 30 L of a mixed solution of ethanol and deionized water in a volume ratio of 1:1, and stirred at a speed of 200 rpm for 6 hours in a 60° C. water bath to obtain a modified solution, and the modified solution was dried in an oven at 80° C. to obtain modified polyvinylidene fluoride.

[0046] Preparation of antioxidant coatings 8 kg of modified polyvinylidene fluoride, 40 kg of epoxy resin and 15 L of solvent were mixed and dispersed to obtain a resin dispersion, 20 kg of metal organic framework corrosion inhibitor and 5 kg of zinc phosphate were added to the resin dispersion, and after stirring at a speed of 500 rpm for 1 hour, the mixture was ground to a fineness of less than 50 μm to obtain an antioxidant coating.

[0047] Preparation of ultra-thin oxidation-resistant stainless steel strip An ultra-thin stainless steel strip substrate is prepared so that the element composition of the ultra-thin stainless steel strip substrate is: nickel 3%, aluminum 7%, zinc 4%, tin 4%, boron 0.075%, bismuth 0.035%, cobalt 0.06%, manganese 2.25%, phosphorus 0.035%, lanthanum 0.08%, and the balance is iron and inevitable impurities.

[0048] The ultra-thin stainless steel strip substrate is polished, and the polished stainless steel strip is immersed in an alkaline solution at 65° C. for 10 minutes to obtain a deoiled stainless steel strip, wherein the alkaline solution is obtained by mixing 5 kg of sodium hydroxide and 1 kg of sodium bicarbonate and dispersing them in 100 L of deionized water; the deoiled stainless steel strip is immersed in a 0.1 mol / L hydrochloric acid solution for 2 minutes to obtain an acid-washed stainless steel strip, and the acid-washed stainless steel strip is washed with deionized water, and dried at 40° C. to obtain a pretreated stainless steel strip.

[0049] 9kg zinc sulfate, 5kg nickel sulfamate, 2kg sodium tungstate, 2kg sodium hypophosphite, 6kg sodium citrate, 3kg boric acid and 8g sodium dodecyl sulfate were mixed and dispersed in 100L deionized water, and stirred at 200rpm for 1h to obtain a plating solution. A lead plate was used as an anode, and a pretreated stainless steel strip was used as a cathode. The strip was immersed in the plating solution for electroplating. The current density was controlled to be 3A / dm2, the electroplating temperature was 60℃, and the electroplating time was 75min. After the electroplating was completed, it was washed with deionized water and dried to obtain a stainless steel strip with an electroplated corrosion-resistant layer.

[0050] The antioxidant coating and the curing agent were mixed in a mass ratio of 20:1 and coated on the surface of the stainless steel strip with the electroplated corrosion-resistant layer. After the coating was dried, it was cured at 100°C for 2h to obtain an ultra-thin antioxidant stainless steel strip.

[0051] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of benzotriazole used is 4.3 kg, the amount of 5-tert-butylisophthalic acid used is 4.09 kg, the amount of zinc nitrate hexahydrate used is 21.51 kg, and the amount of graphene oxide used is 0.1 kg.

[0052] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of benzotriazole used is 4.27 kg, the amount of 5-tert-butylisophthalic acid used is 4.06 kg, the amount of zinc nitrate hexahydrate used is 21.35 kg, and the amount of graphene oxide used is 0.32 kg.

[0053] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that graphene oxide is not added when preparing the metal organic framework material in Example 6.

[0054] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the metal organic framework material is replaced with ZIF-8 when preparing the metal organic framework material corrosion inhibitor.

[0055] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, modified polyvinylidene fluoride is replaced by polyvinylidene fluoride when preparing the antioxidant coating.

[0056] Example 9 Example 9 is based on Example 3, and the only difference between Example 9 and Example 3 is that sodium hypophosphite is not added to the plating solution in Example 9.

[0057] Example 10 Example 10 is based on Example 3, and the only difference between Example 10 and Example 3 is that sodium tungstate is not added to the plating solution in Example 10.

[0058] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, nickel sulfamate in the plating solution is replaced by nickel sulfate.

[0059] Example 12 Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that the electroplating temperature when preparing the electroplated corrosion-resistant layer in Example 12 is 30°C and the electroplating time is 120 minutes.

[0060] Embodiment 13 Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that the electroplating temperature for preparing the electroplated corrosion-resistant layer in Example 13 is 90°C and the electroplating time is 30 minutes.

[0061] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, no electroplated corrosion-resistant layer is prepared.

[0062] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that no anti-oxidation coating is prepared in Comparative Example 2.

[0063] Performance testing (1) Select "GB / T228-2021 Metal Material Room Temperature Tensile Test Method" as the standard, apply tension through a tensile testing machine, gradually increase the tension, and record the maximum stress value before the sample breaks, which is the tensile strength. Prepare three samples for each sample, take the average value after measurement, and record the results in Table 1.

[0064] (2) GB / T19746-2018 Metal and Alloy Corrosion Salt Solution Immersion Test was selected as the standard to prepare the test specimens. The specimens were immersed in a simulated humid atmospheric environment. The test solution contained an aqueous solution of 1 g / L acetic acid and 1 g / L formic acid. After immersion for 3 weeks, the corrosion depth of the specimens was tested, the corrosion rate was calculated, and the corrosion conditions of the specimens were observed and recorded. The results are recorded in Table 1.

[0065] (3) GB / T13303-1991 Method for Determination of Oxidation Resistance of Steel was selected as the standard, and three samples were prepared for the experiment. They were cured at 800°C for 500 h, and the oxidation rate of the samples was tested and calculated. The average value was taken after measurement, and the results are recorded in Table 1.

[0066] Table 1 Test results of strength and oxidation resistance of stainless steel strip It can be seen from Table 1 that the tensile strength of Examples 1-3 is greater than 746 MPa, the corrosion rate is less than 0.009 mm / a, and the oxidation rate is less than 0.003 g / m 2 ·h, it can be seen that the stainless steel strip prepared in the present application has good tensile strength, corrosion resistance and oxidation resistance.

[0067] As can be seen from Table 1, the only difference between Examples 4 and 5 and Example 3 is that in Example 4, the mass ratio of benzotriazole, 5-tert-butylisophthalic acid, zinc nitrate hexahydrate and graphene oxide is 0.2:0.19:1:0.005, and in Example 5, the mass ratio of benzotriazole, 5-tert-butylisophthalic acid, zinc nitrate hexahydrate and graphene oxide is 0.2:0.19:1:0.015. Compared with Example 3, Examples 4 and 5 have decreased tensile strength, corrosion resistance and antioxidant properties; this is because the mass ratio of benzotriazole, 5-tert-butylisophthalic acid, zinc nitrate hexahydrate and graphene oxide is not within the specified range, and too much or too little graphene will affect the structure and properties of the metal organic framework material, thereby affecting the active and passive anti-corrosion properties, and the tensile strength, corrosion resistance and antioxidant properties of the stainless steel strip are reduced.

[0068] As can be seen from Table 1, the only difference between Examples 6, 7, and 8 and Example 3 is that: in Example 6, graphene oxide is not added when preparing the metal organic framework material, in Example 7, the metal organic framework material is replaced with ZIF-8 when preparing the metal organic framework material corrosion inhibitor, and in Example 8, the modified polyvinylidene fluoride is replaced with polyvinylidene fluoride when preparing the antioxidant coating. Compared with Example 3, Examples 6, 7, and 8 have reduced tensile strength, corrosion resistance, and antioxidant properties; this is because if graphene oxide is not added, there is a lack of passive protection, and the corrosion protection effect deteriorates; the metal organic framework material is replaced by ZIF-8, and the ligand of ZIF-8 lacks corrosion inhibition; the modified polyvinylidene fluoride is replaced by polyvinylidene fluoride, there is a lack of modification, the reactivity and compatibility are reduced, the stability and hydrophobicity of the coating are reduced, and thus the tensile strength, corrosion resistance, and antioxidant properties are reduced.

[0069] As can be seen from Table 1, the only difference between Examples 9, 10, and 11 and Example 3 is that in Example 9, sodium hypophosphite is not added to the plating solution, in Example 10, sodium tungstate is not added to the plating solution, and in Example 11, nickel sulfamate in the plating solution is replaced with nickel sulfate. Compared with Example 3, Examples 9, 10, and 11 have reduced tensile strength, corrosion resistance, and oxidation resistance. This is because the replacement and deletion of components in the plating solution will affect the composition, crystal phase structure, and grain size of the alloy coating, thereby affecting the stability and oxidation resistance of the alloy coating, and the tensile strength, corrosion resistance, and oxidation resistance of the stainless steel strip are reduced.

[0070] It can be seen from Table 1 that the only difference between Examples 12 and 13 and Example 3 is that the electroplating temperature when preparing the electroplated corrosion-resistant layer in Example 12 is 30°C and the electroplating time is 120 min, and the electroplating temperature when preparing the electroplated corrosion-resistant layer in Example 13 is 90°C and the electroplating time is 30 min. Compared with Example 3, Examples 12 and 13 have reduced tensile strength, corrosion resistance and antioxidant properties. This is because adjusting the electroplating temperature and time will affect the crystal phase distribution and thickness of the coating, and further affect the stabilizer and durability of the coating, thereby reducing the tensile strength, corrosion resistance and antioxidant properties.

[0071] As can be seen from Table 1, the only difference between Comparative Examples 1 and 2 and Example 3 is that no electroplated corrosion-resistant layer is prepared in Comparative Example 1, and no antioxidant coating is prepared in Comparative Example 2. Compared with Example 3, the tensile strength, corrosion resistance and antioxidant properties of Comparative Examples 1 and 2 are significantly reduced; this is because no electroplated corrosion-resistant layer or antioxidant coating is prepared, the toughening effect of the plating layer or coating is lacking, and the reduction of the protective layer will cause the corrosive medium to penetrate into the interior of the stainless steel strip through the weak points, thereby reducing the tensile strength, corrosion resistance and antioxidant properties.

[0072] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. An ultra-thin anti-oxidation stainless steel strip, characterized in that: The invention comprises an ultra-thin stainless steel strip substrate, an electroplated corrosion-resistant layer and an anti-oxidation coating. The ultra-thin stainless steel strip substrate comprises the following components in mass fractions: 2.5-3.5% nickel, 6-8% aluminum, 3.5-4.5% zinc, 2-6% tin, 0.05-0.1% boron, 0.02-0.05% bismuth, 0.05-0.07% cobalt, 1.5-3% manganese, 0.02-0.05% phosphorus, 0.06-0.1% lanthanum, and the balance is iron and inevitable impurities.

2. The ultra-thin anti-oxidation stainless steel strip according to claim 1, characterized in that: The anti-oxidation coating is obtained by coating the anti-oxidation coating on the surface of the electroplated corrosion-resistant layer. The raw materials for preparing the anti-oxidation coating include metal organic framework material corrosion inhibitor, modified polyvinylidene fluoride, zinc phosphate, epoxy resin and solvent.

3. The ultra-thin anti-oxidation stainless steel strip according to claim 2, characterized in that: The raw materials for preparing the metal organic framework material corrosion inhibitor include metal organic framework material and corrosion inhibitor. The raw materials for preparing the metal organic framework material include benzotriazole, 5-tert-butylisophthalic acid, zinc nitrate hexahydrate and graphene oxide. The corrosion inhibitor includes 8-hydroxyquinoline.

4. The ultra-thin anti-oxidation stainless steel strip according to claim 3, characterized in that: The mass ratio of the benzotriazole, 5-tert-butylisophthalic acid, zinc nitrate hexahydrate and graphene oxide is 0.2:0.19:1:(0.008-0.012).

5. The ultra-thin anti-oxidation stainless steel strip according to claim 2, characterized in that: The modified polyvinylidene fluoride is prepared by the following steps: The polyvinylidene fluoride and sodium hydroxide are dispersed in an ethanol aqueous solution and heated and stirred to react to obtain a modified solution, and the modified solution is dried under heating conditions to obtain modified polyvinylidene fluoride.

6. The ultra-thin anti-oxidation stainless steel strip according to claim 1, characterized in that: The ultra-thin anti-oxidation stainless steel strip is prepared by the following steps: Preparing an ultra-thin stainless steel strip substrate; pre-treating the ultra-thin stainless steel strip substrate, polishing, degreasing, pickling, washing and drying to obtain a pre-treated stainless steel strip; The pretreated stainless steel strip is immersed in a plating solution for electroplating to obtain a stainless steel strip having an electroplated corrosion-resistant layer; The anti-oxidation coating and curing agent are mixed and coated on the surface of the stainless steel strip with the electroplated corrosion-resistant layer. After the coating is dried, it is heated and cured to obtain an ultra-thin anti-oxidation stainless steel strip.

7. The ultra-thin anti-oxidation stainless steel strip according to claim 6, characterized in that: The electroplated corrosion-resistant layer includes zinc, nickel, phosphorus and tungsten.

8. The ultra-thin anti-oxidation stainless steel strip according to claim 7, characterized in that: The plating solution comprises zinc sulfate, nickel sulfamate, sodium tungstate, sodium hypophosphite, sodium citrate, boric acid and sodium dodecyl sulfate.

9. The ultra-thin anti-oxidation stainless steel strip according to claim 8, characterized in that: The electroplated corrosion-resistant layer is prepared by the following steps: The lead plate is used as the anode and the pretreated stainless steel strip is used as the cathode. The strip is immersed in the plating solution for electroplating operation. The temperature and time are controlled. After the electroplating is completed, the strip is washed with water and dried to obtain a stainless steel strip with an electroplated corrosion-resistant layer.

10. The ultra-thin anti-oxidation stainless steel strip according to claim 9, characterized in that: The electroplating temperature is 50-70° C., and the electroplating time is 60-90 min.

Citation Information

Patent Citations

  • Preparation method and application of medical magnesium-based metal coating with stress-corrosion-resisting and self-repairing functions

    CN109675120A

  • Low-temperature-resistant alloy steel end socket and preparation process thereof

    CN118027765A

  • Corrosion-resistant stainless steel band

    CN118547216A

  • Steel having metallic coating and excellent in corrosion resistance

    JP2002060978A

  • Hot-dip galvanized steel sheet superior in weldability and manufacturing method therefor

    JP2002194518A

Cited By

  • Corrosion-resistant flexible ultrathin stainless steel band and processing technology thereof

    CN121381106A